Understanding the challenge of gender equity in China: a preliminary study - Preston, Alison; Lord, Linley (EBSCO Publishing and Gale Group/ Thomson Publishing, 2008)
Since embracing market economy principles and opening to the global economy China has achieved astonishing economic growth although many are questioning the ability of the current model to generate sustained productivity growth. Already China is experiencing acute skill shortages amongst particular groups of labour (eg. skilled managerial labour), notwithstanding the presence of a number of unemployment business and management graduates. Commentators are now questioning the role of institutions and gender equity as a way of engendering sustainable productivity growth. Building on this framework this paper uses a mixed methods approach to explore the question of gender equity in China. Although only a preliminary study the paper provides important insights into the inherent masculine bias in China and the consequent effects on the employment and career prospects of women. If China is to overcome the forecast labour shortages for professional managers it needs to be able to offer the same opportunities to women as men; it needs to be able to offer wide acceptance as women as general managers and it needs to overcome discriminatory practices that currently disadvantage women.